2021
DOI: 10.1042/bcj20210375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type II LRRK2 inhibitors on signaling and mitophagy

Abstract: Much effort has been devoted to the development of selective inhibitors of the LRRK2 as a potential treatment for LRRK2 driven Parkinson's disease. In this study we first compare the properties of Type I (GSK3357679A and MLi-2) and Type II (GZD-824, Rebastinib and Ponatinib) kinase inhibitors that bind to the closed or open conformations of the LRRK2 kinase domain, respectively. We show that Type I and Type II inhibitors suppress phosphorylation of Rab10 and Rab12, key physiological substrates of LRRK2 and als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 69 publications
5
50
1
Order By: Relevance
“…The latter has been confirmed in peripheral blood from heterozygous LRRK2 -R1441G mutation carriers with and without PD ( 47 ). Phosphorylation of serine 935 of LRRK2 (pSer935-LRRK2) has historically been an important biomarker site and while it is not a direct autophosphorylation site, does not correlate with LRRK2 kinase activity, it dephosphorylates in response to Type I but not with Type II small molecule LRRK2 inhibitors and likely informs on the confirmation of the LRRK2 kinase domain ( 25, 48 ). We investigated pThr73-Rab10 and pSer935-LRRK2 levels in PBMCs from the MJFF FBN cohort with largely the same subjects that were analyzed for mtDNA damage (Table S6, Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been confirmed in peripheral blood from heterozygous LRRK2 -R1441G mutation carriers with and without PD ( 47 ). Phosphorylation of serine 935 of LRRK2 (pSer935-LRRK2) has historically been an important biomarker site and while it is not a direct autophosphorylation site, does not correlate with LRRK2 kinase activity, it dephosphorylates in response to Type I but not with Type II small molecule LRRK2 inhibitors and likely informs on the confirmation of the LRRK2 kinase domain ( 25, 48 ). We investigated pThr73-Rab10 and pSer935-LRRK2 levels in PBMCs from the MJFF FBN cohort with largely the same subjects that were analyzed for mtDNA damage (Table S6, Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Nine variants [ROC (N1437H, R1441G/C/S/H, A1442P) and COR B (Y1699C, S1761R, L1795F)], increased Ser1292 autophosphorylation 2- to 4-fold (Fig 2A, Fig 3A, D, SFig 1). Previous work revealed that variants that activate LRRK2 kinase activity such as ROC (R1441G/C) and COR B (Y1699C) suppressed LRRK2 biomarker phosphorylation, likely by promoting the closed, active conformation of the LRRK2 kinase domain [2527]. Consistent with this, 10 activating variants [ROC (N1347H, R1441G/H/S, A1442P, V1447M), COR B (Y1699C, L1795F), kinase (I2020T) and WD40 (G2385R)], displayed >2-fold reduction in phosphorylation of all biomarker sites (Fig 2B, Fig 3A, E, SFig 1).…”
Section: Resultsmentioning
confidence: 99%
“…This has been proposed to disrupt vesicle trafficking by causing a "roadblock" for microtubule-based motors [6,9]. The closed, active conformation of LRRK2 also leads to the dephosphorylation of a cluster of phosphorylation sites (Ser910, Ser935, Ser955 and Ser973) located between the Hinge helix and LRR domain through an unknown mechanism [25][26][27]. Certain pathogenic mutations such as G2019S (located within the kinase domain) promote autophosphorylation of LRRK2 at Ser1292 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Type II kinase inhibitors inhibit LRRK2 kinase activity while maintaining an open LRRK2 conformation, therefore complementing the limitation of type I inhibitors. Recently, several type II kinase inhibitors, such as GZD-824 [ 190 ] and Rebastinib [ 191 ], were found to inhibit LRRK2 kinase activity, as they suppressed Rab10 phosphorylation while preventing aberrant LRRK2 binding to microtubule filaments [ 193 ]. However, both GZD-824 and Rebastinib were initially developed for treatments of leukemia [ 194 ], and they show poor selectivity for LRRK2 [ 193 ].…”
Section: Main Textmentioning
confidence: 99%
“…Recently, several type II kinase inhibitors, such as GZD-824 [ 190 ] and Rebastinib [ 191 ], were found to inhibit LRRK2 kinase activity, as they suppressed Rab10 phosphorylation while preventing aberrant LRRK2 binding to microtubule filaments [ 193 ]. However, both GZD-824 and Rebastinib were initially developed for treatments of leukemia [ 194 ], and they show poor selectivity for LRRK2 [ 193 ]. Therefore, development of novel type II inhibitors with high selectivity towards LRRK2 remains a big challenge for advancement of LRRK2 kinase inhibitors in PD therapeutics.…”
Section: Main Textmentioning
confidence: 99%